Evaluation of the DOAC-Stop® Procedure to Overcome the Effect of DOACs on Several Thrombophilia Screening Tests - Favresse, Julien; Lardinois, Benjamin; Sabor, Lina; Devalet, Bérangère; Vandepapeliere, Julie; Braibant, Maximilien; Lessire, Sarah; Chatelain, Bernard; Jacqmin, Hugues; Douxfils, Jonathan; Mullier, François (TH Open, 2018)
The impact of direct oral anticoagulants (DOACs) on laboratory assays used for thrombophilia testing (e.g., antithrombin, protein S, protein C, lupus anticoagulant and activated protein-C resistance) is a well-known issue and may cause false-positive and -negative results. Therefore, the correct interpretation of tests that are performed in patients taking DOACs is mandatory to prevent misclassification and the subsequent clinical consequences. We aimed at evaluating the efficiency of a new and simple procedure (DOAC-Stop®; Haematex Research, Hornsby, Australia) to overcome the effect of all DOACs in real-life settings and to assess the percentage of erroneous results due to the presence of DOACs on thrombophilia screening tests. For this purpose, 135 DOAC-treated patients (38 apixaban, 40 dabigatran, 15 edoxaban, and 42 rivaroxaban) and 20 control patients were enrolled. A significant drop in apixaban, dabigatran, edoxaban, and rivaroxaban plasma concentrations following the DOAC-Stop® treatment was observed (74.8–8.2 ng/mL [p < 0.0001], 95.9–4.7 ng/mL [p < 0.0001], 102.1–8.8 ng/mL [p = 0.001], and 111.3–7.0 ng/mL [p < 0.0001], respectively). The DOAC-Stop® treatment was mostly effective to overcome the effect of DOACs on PTT-LA, dilute Russell's viper venom time (dRVVT) screen, and dRVVT confirm tests. Using our procedures, false-positive results due to DOACs were observed only with lupus anticoagulant tests (up to 75%) and fell to zero after the DOAC-Stop® procedure, regardless of the DOAC considered. In conclusion, the DOAC-Stop® adsorbent procedure appeared to be an effective and simple way to overcome the interference of DOAC on coagulation tests and should facilitate the interpretation of thrombophilia screening tests in patients taking DOACs.
Keywords: thrombophilia; direct oral anticoagulants; interference